Naming Culinary in Mandailing Society: A Culinary Linguistic Approach - Rahmawati Rahmawati; Mulyadi Mulyadi (BIRCU, 2021)
This study examines culinary naming in the mandailing community. This study aims to see what culinary names exist in the Mandailing community according to the theory used. This research involves a concept or meaning, a word or symbol and something that is referred to as the relation between the elements described in the 'meaning triangle' pioneered by Ogden and Richard. This research is expected to be a reference for the Mandailing community to find out the meaning and type of culinary with a qualitative descriptive method. Data collection techniques using Spradley's ethnographic model using interviews and participant observation methods. The results showed that there were 8 culinary names for the mandailing community.